(untitled) (Research, Society and Development, 2021)
Objective of the work was to perform the spatialization of the monthly and annual erosivity of the hydrographic basin of Córrego Fundo, Aquidauana-MS, through the use of a Geographic Information Systems. For the characterization of rainfall and erosivity, historical series of 28 years were considered, corresponding to the years 1991-2019 of 5 weather stations belonging to the hydrometeorological network of the National Agency and 1 station of CEMTEC / MS - in the period 2008-2018. The erosivity determination was made according to the potential equation adjusted for the municipality of Campo-Grande, MS and later spatialized for the entire basin, using ArcGis PRO 2.5.2 software. The average annual erosivity ranged from 7749.29 to 7800.55 MJ mm ha-1 h-1 year, with an average erosivity of 7,781 MJ mm ha-1 h-1 year. The months of greatest erosivity are related to the rainy periods in the region. Some months of the year, monthly erosivity was rated very low to low, however the average annual erosivity was considered high. The results of this work present relevant information to support the planning of soil and water conservation, as it was possible to verify, throughout the year, the months that present the greatest susceptibility to erosion.